Retinal Vessel Diameter Reductions Are Associated with Retinal Ganglion Cell Dysfunction, Thinning of the Ganglion Cell and Inner Plexiform Layers, and Decreased Visual Field Global Indices in Glaucoma Suspects - Andrew Tirsi; Nicholas Leung; Rohun Gupta; Sungmin Hong; Derek Orshan; Joby Tsai; Corey Ross Lacher; Isabella Tello; Samuel Potash; Timothy Foster; Rushil Kumbhani; Celso Tello (Diagnostics, 2025)
Background/Objectives: The aim of this study was to evaluate the associations between optical coherence tomography angiography (OCTA)-based retinal vessel diameter (RVD) measurements, with retinal ganglion cell (RGC) function assessed by means of steady-state pattern electroretinography (ssPERG) using ganglion cell layer-inner plexiform layer thickness (GCL-IPLT) measurements and with Humphrey field analyzer (HFA) global indices in glaucoma suspects (GSs). Methods: Thirty-one eyes (20 participants) underwent a comprehensive ophthalmologic examination, ssPERG measurements utilizing the PERGLA paradigm, HFA, optical coherence tomography (OCT), and OCTA. The OCTA scans were processed using ImageJ software, Version 1.53, allowing for measurement of the RVD. Multiple linear regression models were used. Results: After controlling for age, race, central corneal thickness (CCT), and spherical equivalent (SE), a linear regression analysis found that the RVD explained the 4.7% variance in magnitude (Mag) (p = 0.169), 9.2% variance in magnitudeD (MagD) (p = 0.021), and 16.9% variance in magnitudeD/magnitude (p = 0.009). After controlling for age, CCT, and signal strength (SS), a linear regression analysis found that the RVD was significantly associated with the GCL-IPLT measurements (average GCL-IPL, minimum GCL-IPL, superior, superonasal, inferior, and inferonasal sectors) (p ≤ 0.023). An identical regression analysis where the RVD was replaced with the PERG parameters showed a significant association between the MagD and almost all GCI-IPLT measurements. RVD measurements were significantly associated with HFA VFI 24-2 (p = 0.004), MD 24-2 (p < 0.001), and PSD 24-2 (p = 0.009). Conclusions: Decreased RVD measurements were significantly associated with RGC dysfunction, decreased GCL-IPLT, and all HFA global indices in the GSs.